Facile preparation of a V2O3/carbon fiber composite and its application for long-term performance lithium-ion batteries. (26th May 2017) - Liu, Xinping; Liu, Renpin; Zeng, Lingxing; Huang, Xiaoxia; Chen, Xi; Zheng, Cheng; Xu, Yuxian; Qian, Qingrong; Wei, Mingdeng; Chen, Qinghua
Abstract : A V2 O3 /carbon-nanofiber composite was initially synthesized, which exhibited large reversible capacity and excellent long-term cycling performance for lithium-ion batteries. Abstract : In the present work, a vanadium-trioxide/carbon-nanofiber composite (V2 O3 /CNF), integrated with different amounts of V2 O3, was synthesized by a simple approach. After a simple combined electrospinning and carbonization process, V2 O3 nanoparticles were successfully distributed through carbon fibers. Due to the synergistic effect between V2 O3 and carbon, V2 O3 /CNF as an anode of lithium-ion batteries (LIBs) exhibits high reversible capacity and excellent long-term cycling stability. The content of V2 O3 is of great importance to the electrochemical performance. The V2 O3 /CNF with the optimized content of V2 O3 (57 wt%) shows a capacity of 544 mA h g −1 at a current density of 0.5 A g −1 after 500 cycles. More importantly, a capacity of 204 mA h g −1 at a high current density of 4 A g −1 can be retained after 1000 cycles.